Use of fluoxetine to reduce weight in adults with overweight or obesity: Abridged republication of the Cochrane Systematic Review - Aurora E. Serralde-Zuñiga; Alejandro G. González-Garay; Yanelli Rodríguez-Carmona; Guillermo Meléndez-Mier (Obesity Facts, 2022)
Introduction: Using fluoxetine is one of many weight-loss strategies. A serotonin reuptake inhibitor indicated for depression believed to impact weight control by changing an individual’s appetite; however, its benefit-risk ratio is unclear. The aim of this review is to assess the efficacy and safety of fluoxetine in reducing weight in adults with overweight or obesity. Methods: We searched Cochrane Library, MEDLINE, Embase and other databases without language restrictions. Cochrane Collaboration tool and GRADE instrument assessed the risk of bias of randomised controlled trials and certainty of their evidence. We conducted random-effects meta-analyses and calculated the risk ratio/mean difference with 95% confidence intervals for the outcomes. Results: We included 19 trials (2,216 adults) and found that fluoxetine may reduce weight by −2.7 kg (95% CI −4 to −1.4; P < 0.001) and body mass index (BMI) by −1.1 kg/m2 (95% CI −3.7 to 1.4), compared with placebo; however, it would cause approximately twice as many adverse events, such as dizziness, drowsiness, fatigue, insomnia or nausea. Conclusions: Although low-certainty evidence suggests that off-label fluoxetine may reduce weight, high-certainty research is needed to be conducted in the future to determine its effects exclusively as well as whether it is useful when combined with other agents.